2018
DOI: 10.1177/0194599818764349
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Molecular Features of Allergic Fungal Rhinosinusitis

Abstract: Objective Allergic fungal rhinosinusitis (AFRS) is a clinical subtype of chronic rhinosinusitis with nasal polyps (CRSwNP), characterized by eosinophilic mucin, evidence of fungal elements within the mucin, fungal-specific type I hypersensitivity, and characteristic computed tomography findings. It remains controversial whether AFRS represents a disease with a unique pathophysiology from chronic rhinosinusitis or is merely a severe form of CRSwNP. The goal of this study was to identify molecular features uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Because the induction of intracellular calcium signaling in primary SNECs by A. fumigatus has not been explored, it remains to be determined if A. fumigatus also upregulates IL‐33 expression by using PAR2 to activate CRACs. The upregulation of several calcium‐related signaling pathways and receptors in CRSwNP was recently reported; this signaling modality will be the subject of future investigations. Calcium‐related signaling pathways in response to fungal protease interactions represent potential novel therapeutic targets for the treatment of CRSwNP.…”
Section: Discussionmentioning
confidence: 81%
“…Because the induction of intracellular calcium signaling in primary SNECs by A. fumigatus has not been explored, it remains to be determined if A. fumigatus also upregulates IL‐33 expression by using PAR2 to activate CRACs. The upregulation of several calcium‐related signaling pathways and receptors in CRSwNP was recently reported; this signaling modality will be the subject of future investigations. Calcium‐related signaling pathways in response to fungal protease interactions represent potential novel therapeutic targets for the treatment of CRSwNP.…”
Section: Discussionmentioning
confidence: 81%
“…In less prevalent cases, endotypes of CRS may be related to well‐defined mechanisms of disease that can be delineated using clinical knowledge. For example, AFRS may represent a distinct endotype of CRS that is defined as rhinosinusitis produced through a chronic allergic reaction to ambient fungal elements that may reach or colonise the paranasal sinus cavities . CRS in the setting of eosinophilic granulomatosis with polyangiitis (EGPA) may also be considered a distinct CRS endotype defined by sinus disease caused by the underlying vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also reveal that the expression of histatins negatively correlates with the expression of several type 2 inflammatory mediators, including IL-13RA1, IL-4R, and periostin. 15 Taken together, disruptions in innate immune signaling and epithelial barrier function appear to go hand-in-hand with the pronounced type 2 inflammation observed in AFRS. Future studies will elucidate the mechanisms surrounding decreased barrier protein expression in AFRS, whether this is the result of specific cytokine-mediated suppression, an inciting factor in Th2 inflammation, defect in activation of antifungal pathways, or a combination of mechanisms.…”
Section: Innate Immune Dysregulation In Afrsmentioning
confidence: 99%
“…Several works from the group of the senior author have demonstrated the incidence of comorbid asthma to be nearly half of that of CRSwNP. 10 , 13 , 14 , 15 For instance, in a prospective study of 410 patients, Promsopa et al 14 recently used pulmonary function testing (PFT) to evaluate the prevalence of asthma CRS subtypes. This study found 23.6% of AFRS patients as compared to 48.3% of CRSwNP patients with PFT-confirmed asthma.…”
Section: Epidemiology Of Afrsmentioning
confidence: 99%
See 1 more Smart Citation